Estudio Técnico-Económico para la instalación de una planta procesadora de conservas de palmito de pijuayo (Bactris gasipaes H.B.K.J.) En el dsitrito de yurimaguas provincia de alto amazonas - Vela Pinedo Merige (2013)
With knowledge of the exceptional conditions of the ecosystem of the area of Pampa Hermosa, such as microclimate, soil, moisture, temperature, relative humidity and rainfall is very important for the development of farming on a large scale place, as an alternative to move the illegal cultivation of coca in the lowland, and to meet the objectives of this project, the implementation of this Technical-economic study for the installation of processing plant palm preserved from pijuayo planned; the final product will be mainly oriented to foreign markets. The canned palm is highly regarded as exotic food in developed its gastronomic value cholesterol-free countries. The potential demand currently unmet worldwide is estimated at 8,000 MT, while in the country the consumption volume is small, just less than 10 %, so all production will be for export for national currencies much needed our country for the development of the social infrastructure ( PROM PES 2000). Making an analysis of international market has given to Europe as the most attractive market, being huge and have larger commercial facilities, and offer higher prices, also identified other major consumers such as: USA, Canada, Japan, Uruguay, Argentina and Chile. The machinery and equipment required for the project is offered in the domestic market, ensuring the installation of the plant, proposing its location in the village of Pampa Hermosa, Yurimaguas District, Province of Upper Amazon, which meet the requirements of first priority. The physical requirement of the processing plant will be 20,000 m2 of which 504 m2 is engaged in the construction of the plant and other areas will be for future expansion of the plant. The total investment cost for the installation of the agro industrial plant reaches the amount of U.S. $ 680317 equivalent to S/ 1904888 soles, of which $ 417337 will be allocated to fixed investment tangible, $ 31871 deferred and $ 231079 investment capital job. Of the total• investment of $ 68031780 % will be financed by the regional govemment of Loreto through the regional program of agriculture credit (PROCREA) at an interest rate of 6 % per annum and a repayment period of 7 years. The plant started production with an initial capacity of 60 % of installed capacity in 2015 with a production of 1073495 tins of palm tipi % (medium) and a net income $ 412,984 equivalent to SI 1156355. The unit cost of processing presentation with a net weight of 0.400 kg. is $ 1.25/ late and a profit margin of 1 O %, the production cost reaches $ 1.37 and more taxes for being an export product, canned palm hearts will be sold at a retail price of $ 1.63 per can equivalent S/ 4.50 . For purposes of economic and financial flows assessment and cost benefit is observed that dollarized planned far projection FOB average selling price of $ 2.18/kg USA. that will be offered to European countries like England, Germany, France and Spain; positive net flows is obtained from the first year of operations the global economic and financial ratios evaluation show the feasibility of the project weigh out for an opportunity cost 4 % annual of the dollars invested as own contribution and 6% will be charged by the regional government of Loreto through PROCREA. lndicators of economic and financial evaluation of the project showed a positive, such as profitability VANE = 6719579, VANF = 5451313, TIRE= 150 %.TIRF = 494 %, B/C( E)= 1.72 ,B/C( F) = 1.59 , with a recovery period of 2 years, 11 months and 18 days indicators that provide security, further improve the quality of life and income of rural farmers in the lowland.